Dietary fiber consumption and outcomes of different cancers: an umbrella review - Xingyu He; Jiayi Hou; Lei Liu; Xin Chen; Lijie Zhang; Caojia Pang; Yu Tong; Hongling Li; Feng Chen; Rong Peng; Zheng Shi (Food & Nutrition Research)
Background: The relationship between dietary fiber intake and cancer outcomes, including incidence, recurrence, and mortality, is crucial for understanding cancer prevention strategies. Methods: An umbrella review was conducted, analyzing existing systematic reviews and meta-analyses from PubMed, Embase, and the Cochrane Database of Systematic Reviews. This included data from 26 meta-analyses based on 2,107 unique articles, covering 52 observational study outcomes. The quality of the studies was assessed using the AMSTAR 2 tool. Results: High fiber intake significantly lowers the risk of cancers affecting the digestive, reproductive, and urinary systems, including esophageal adenoma, squamous cell carcinoma, gastric, pancreatic, colon, rectal, colorectal adenoma, breast, ovarian, endometrial, prostate, renal cell, and bladder cancers. Findings estimated that the risk of Colon cancer between total dietary fiber (TDF) was 0.74 (95% confidence interval [CI]: 0.67–0.82), and the risk of Colorectal cancer between TDF was 0.88 (95% CI: 0.82–0.94). TDF was also found to be protective against Barrett’s esophagus and esophagus cancer, esophageal adenomas, and esophagus squamous cell carcinoma, with effect sizes of 0.52 (95% CI: 0.43–0.64), 0.50 (95% CI: 0.37–0.67), and 0.53 (95% CI: 0.31–0.90), respectively. Conversely, increased intake of cereal fiber was associated with a higher incidence of renal cell carcinoma and endometrial cancer. Dose–response analyses revealed that increments of 2.5, 5, or 10 g per day in dietary fiber could lead to different levels of risk reduction for these cancers. Meta-regression suggested an optimal fiber intake range of 7–36 g per day for colon cancer prevention. However, the overall study quality was predominantly rated as ‘very low’. Conclusions: Higher dietary fiber intake is linked to reduced cancer risk and improved outcomes. These findings highlight dietary fiber’s importance in cancer prevention and care.